2014
DOI: 10.20532/ccvw.2014.0001
|View full text |Cite
|
Sign up to set email alerts
|

Fast Localization of Facial Landmark Points

Abstract: Localization of salient facial landmark points, such as eye corners or the tip of the nose, is still considered a challenging computer vision problem despite recent efforts. This is especially evident in unconstrained environments, i.e., in the presence of background clutter and large head pose variations. Most methods that achieve state-of-the-art accuracy are slow, and, thus, have limited applications. We describe a method that can accurately estimate the positions of relevant facial landmarks in real-time e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…To validate the strength of the proposed new even system further, we validate it on the widely used BioID dataset [56], where it obtains a 100% detection rate with a limited number of false positives. Our best ensemble/filter combination outperforms the method proposed by Markuš et al [34], which has been shown to surpass the performance of these well-known state-of-the-art commercial face detection systems: Google Picasa, Face++, and Intel Olaworks.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…To validate the strength of the proposed new even system further, we validate it on the widely used BioID dataset [56], where it obtains a 100% detection rate with a limited number of false positives. Our best ensemble/filter combination outperforms the method proposed by Markuš et al [34], which has been shown to surpass the performance of these well-known state-of-the-art commercial face detection systems: Google Picasa, Face++, and Intel Olaworks.…”
Section: Introductionmentioning
confidence: 74%
“…We perform experiments on the fusion of six face detectors: the four detectors tested in [9] (the canonic VJ algorithm [14], a method using the Split up sparse Network of Winnows (SN) classifier [31], a modification of the VJ algorithm with fast localization (FL) [34], and a face detector based on Discriminative Response Map Fitting (DRMF) [32]), as well as two additional face detectors (the VJ modification using NPD features (NPD) [33] and a high-performance method implemented here: . In the following, this latter method is called Single Scale-invariant Face Detector (SFD).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(10) Jurić and Lončarić (11) adopted the method proposed in Ref. 12, which did not require manual parameter adjustments and boasted simpler processes that reduced the amount of computation needed, but the results of that study indicated a low vehicle correction rate. In Ref.…”
Section: Introductionmentioning
confidence: 99%